Existentialist ethical thought in the theatre of Gabriel Marcel, Albert Camus, and Jean-Paul Sartre - Tattam, Helen (2007)
The Existentialist thought of Gabriel Marcel (1889-1973), Albert Camus (1913-1960), and Jean-Paul Sartre (1905-1980) is dominated by a concern for the ethical, and Marcel, Camus, and Sartre all explored questions of morality in the works they produced for the theatre. Not only does this suggest that a particular appreciation of their ethical thought is necessary for their drama to be fully understood; an investigation of their dramatic works might equally provide a privileged access to their ethical thought. The study of Existentialist drama has been somewhat neglected – and what research has been undertaken focuses on the work of the three individual playwrights, rather than offering a comparative analysis. No study to date has focused on Existentialist drama purely in relation to the ethical. Furthermore, existing studies tend to address either the aesthetic or the philosophical dimension of Existentialist theatre. But as this dissertation will argue, theatre is not a straightforward medium of expression; the discussion of a play’s philosophical ‘message’ must take this into account. The aims of the dissertation are to (i) analyse the fundamental concepts applied by Marcel, Camus, and Sartre in the field of ethics; (ii) examine the ways in which each adapts and experiments with the dramatic genre to address ethical issues; (iii) explore and compare the interplay of philosophy and drama in their respective œuvres, in order that theatre’s influence on each philosopher’s ethical voice might be reconsidered. The dissertation will be divided into two major parts: Section 1 will introduce the plays selected for analysis, aiming to identify the ethical discourse present in the theatre of each Existentialist philosopher; Section 2 will then explore the inter-relations between these ethical discourses, and consider how the three Existentialists’ dramatization of the ethical is reflective of their theoretical ethical discussions.